Magnetohydrodynamic Unsteady Convective Heat and Mass Transfer along a Semi-Infinite Permeable Vertical Plate with Heat Absorption (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The study investigates the unsteady, two-dimensional, laminar boundary-layer flow of a viscous, incompressible, electrically conducting, and heat-absorbing fluid past a semi-infinite vertical permeable moving plate. The flow is influenced by a uniform transverse magnetic field, along with thermal and concentration buoyancy effects. The plate moves at a constant velocity in the direction of the fluid motion, while the free-stream velocity follows an exponentially increasing small perturbation law. Time-dependent wall suction is applied at the permeable surface. The dimensionless governing equations are analytically solved using two-term harmonic and non-harmonic functions. The obtained solutions are shown to reduce to previously reported results under special limiting conditions. Numerical evaluation of the analytical expressions is carried out, and graphical illustrations of the velocity, temperature, and concentration distributions within the boundary layer are provided. Additionally, tabulated results for the skin-friction coefficient, Nusselt number, and Sherwood number are presented and discussed.